Evaluation of Surrogate Animal Models of Melioidosis - Warawa, Jonathan M. (Frontiers in Microbiology, 2010)
Burkholderia pseudomallei is the Gram-negative bacterial pathogen responsible for the disease melioidosis. B. pseudomallei establishes disease in susceptible individuals through multiple routes of infection, all of which may proceed to a septicemic disease associated with a high mortality rate. B. pseudomallei opportunistically infects humans and a wide range of animals directly from the environment, and modeling of experimental melioidosis has been conducted in numerous biologically relevant models including mammalian and invertebrate hosts. This review seeks to summarize published findings related to established animal models of melioidosis, with an aim to compare and contrast the virulence of B. pseudomallei in these models. The effect of the route of delivery on disease is also discussed for intravenous, intraperitoneal, subcutaneous, intranasal, aerosol, oral, and intratracheal infection methodologies, with a particular focus on how they relate to modeling clinical melioidosis. The importance of the translational validity of the animal models used in B. pseudomallei research is highlighted as these studies have become increasingly therapeutic in nature.